 # Simplify each expression.1. -n+9n+3-8-8n2. 3(-4x+5y)-3x(2+4)5. 5-4y+x+9y7. -2x+3y-5x-(-8y) Bevan Mcdonald 2021-01-31 Answered

Simplify each expression.
1) $-n+9n+3-8-8n$
2) $3\left(-4x+5y\right)-3x\left(2+4\right)$
3) $5-4y+x+9y$
4) $-2x+3y-5x-\left(-8y\right)$

You can still ask an expert for help

• Questions are typically answered in as fast as 30 minutes

Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it Dora

1) $-n+9n+3-8-8n$

$=\left(-n+9n-8n\right)+\left(3-8\right)$

$=n\left(-1+9-8\right)+\left(3-8\right)$

$=n\left(8-8\right)+\left(-5\right)$

$=nx0+\left(-5\right)=0+\left(-5\right)=-5$
2) $3\left(-4x+5y\right)-3x\left(2+4\right)$

$=3\left(-4x+5y\right)+\left(-3x\right)\left(2+4\right)$

$=3\left(-4x+5y\right)+\left(-3x\right)\left(6\right)$

$=\left(-12x\right)+15y+\left(-18x\right)$

$=15y+\left(-12x+-18x\right)$

$=15y+\left(-30x\right)=15y-30x=15\left(y-2x\right)$
3) $5-4y+x+9y$

$=\left(9y-4y\right)+x+5$

$=y\left(9-4\right)+x+5$

$=5y+x+5$

$=\left(5y+5\right)+x=5\left(y+1\right)+x$
4) $-2x+3y-5x-\left(-8y\right)$

$=-2x+3y-5x+8y$

$=\left(3y+8y\right)+\left(-2x+-5x\right)$

$=y\left(3+8\right)+x\left(-2+-5\right)$

$=11y+\left(-7x\right)=11y-7x$

1) $-5$

2) $15\left(y-2x\right)$

3) $5\left(y+1\right)+x$

4) $11y-7x$

###### Not exactly what you’re looking for? Jeffrey Jordon Jeffrey Jordon Jeffrey Jordon Jeffrey Jordon